ICF Generic Set as new standard for the system wide assessment of functioning in China: a multicentre prospective study on metric properties and responsiveness applying item response theory. Issue 12 (14th December 2018) - Ehrmann, Cristina; Prodinger, Birgit; Stucki, Gerold; Cai, Wenzhi; Zhang, Xia; Liu, Shan; Liu, Shouguo; Li, Jianan; Reinhardt, Jan D
Abstract : Objectives: To examine metric properties and responsiveness of the International Classification of Functioning, Disability and Health (ICF) Generic Set when used in routine clinical practice to assess functioning. Design: Prospective multicentre study. Setting: 50 hospitals from 20 provinces of Mainland China. Participants: 4510 adult inpatients admitted to the departments of Pulmonology, Cardiology, Neurology, Orthopaedics, Cerebral Surgery or Rehabilitation Medicine. Main outcome measures: The ICF Generic Set (ICF Generic 6 Set) applied with an 11-point numeric rating scale (0-no problem to 10-complete problem) was fit to the Partial Credit Model (PCM) to create an interval score of functioning. Results: PCM assumptions were found to be fulfilled after accounting for Differential Item Functioning. With an average improvement by 7.86 points of the metric ICF Generic 6 score (95% CI 7.53 to 8.19), the ICF Generic 6 Set proved sensitive to change (Cohen's f 2 =0.41). Ceiling and floor effects on detecting change in functioning were cancelled or reduced by using the metric score. Conclusion: The ICF Generic 6 Set can be used for the assessment of functioning in routine clinical practice and an interval score can be derived which is sensitive to change.